Two new species of Armascirus (Acari: Prostigmata: Cunaxidae) from Slovakia - Kalúz, Stanislav; Vrabec, Michal (Zootaxa, 2013)
Two new mite species from Central Europe, viz. Armascirus fendai sp. nov. and Armascirus masani sp. nov. (Acari: Prostigmata, Cunaxidae) are described and figured. The keys to the known species (females and males) of the genus Armascirus are given.